2008
DOI: 10.1164/rccm.200712-1901oc
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Ablation of Pre-Bötzinger Complex Disrupts Breathing during Sleep but Not Wakefulness

Abstract: Rationale: In adult rats, bilateral ablation of pre-Bötzinger complex (preBötC) neurokinin 1-expressing (NK1R) neurons leads to a progressive and irreversible disruption in breathing pattern, initially during sleep, eventually resulting in an ataxic breathing pattern during wakefulness. Objectives: Here we determine whether ablation of fewer preBötC NK1R neurons leads to a persistent pattern of disordered breathing during sleep but not during wakefulness. Methods: Adult male Sprague-Dawley rats (n 5 12) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 47 publications
0
53
0
Order By: Relevance
“…Central apneas can also occur as a result of reflex-elicited arrest of the central respiratory rhythm generator (100), or its dysfunction (330,331,349,546), as well as during apneustic states generated experimentally (299) or resulting from neurological and developmental disorders such as Rett Syndrome (253).…”
Section: Upper Airway Motor Control In Central Sleep Apneamentioning
confidence: 99%
“…Central apneas can also occur as a result of reflex-elicited arrest of the central respiratory rhythm generator (100), or its dysfunction (330,331,349,546), as well as during apneustic states generated experimentally (299) or resulting from neurological and developmental disorders such as Rett Syndrome (253).…”
Section: Upper Airway Motor Control In Central Sleep Apneamentioning
confidence: 99%
“…It also highlights the potential insights that can be gained by comparative functional studies between the locomotor and respiratory CPGs with respect to the cellular organization of motor networks in the CNS. Other groups have taken the approach of probing these circuits using genes that are either expressed in the hindbrain rhombomeres from which these CPGs develop or in populations of putative respiratory interneurons (Gray et al , 2001; McKay and Feldman, 2008; Tan et al , 2008; Abbott et al , 2009; Dubreuil et al , 2009; Thoby-Brisson et al , 2009). For example, studies analyzing Phox2b mutant mice have revealed a key role for parafacial/retrotrapezoid nucleus in chemosensitivity (Dubreuil et al , 2009).…”
Section: Genetically-defined Interneuronal Populations That Shape Thementioning
confidence: 99%
“…Opiate-sensitive neurons in the preBötC are active during inspiration, whereas opiate-insensitive neurons in the RTN/pFRG are active during expiration. Recent work has shown that unilateral ablation of the preBötC in rats leads to disrupted breathing during sleep but not wakefulness [34,35]. The output of respiratory motoneurons is therefore dependent upon the complex interaction of peripheral and central chemoreceptors interacting with the pattern generators.…”
Section: Basic Physiology Of Respirationmentioning
confidence: 99%